Identifying the Internal Network Structure of a New Copper Isonicotinate Thin‐Film Polymorph Obtained via Chemical Vapor Deposition. Issue 12 (28th March 2023) - Legenstein, Lukas; Rodríguez‐Hermida, Sabina; Rubio‐Giménez, Víctor; Stassin, Timothée; Hofer, Sebastian; Kainz, Manuel P.; Fratschko, Mario; Carraro, Francesco; Falcaro, Paolo; Ameloot, Rob; Resel, Roland
Abstract: The preparation of thin films is often associated with the appearance of unknown polymorphs, as both the substrate and deposition method can heavily influence crystallization processes. Here, chemical vapor deposition is used to obtain thin films of a copper‐isonicotinate (Cu‐INA) metal–organic framework (MOF). Starting from copper‐based precursor layers (copper oxide and hydroxide), a solid‐vapor conversion with vaporized isonicotinic acid in either a dry or humidified atmosphere, yields a new Cu‐INA MOF polymorph. It is found that the crystalline order of the precursor layer has a strong impact on the texture of Cu‐INA thin films. Furthermore, a novel methodology is introduced to determine the structure of a previously unknown thin‐film phase of Cu‐INA. Although only a few diffraction peaks are found via synchrotron grazing incidence X‐ray diffraction (GIXRD), a triclinic unit cell can be determined, and Patterson functions can be calculated. The latter reveals the position of the copper atoms within the unit cell and the alignment of the INA linkers defining the coordination network structure. This work introduces how the combination of GIXRD data with Patterson functions can be used to identify the structure of an unknown thin‐film MOF polymorph. Abstract : Metal–organic frameworks are ideal candidates for applying Patterson functions to determine the positions of the metal atoms within the crystallographic unit cell. In addition, the internal network structure—defined by the linker molecules—can be identified. The method is applied to solve the crystal structure of a new thin film polymorph of copper‐isonicotinate.